The Probiotic Escherichia coli Nissle 1917 Enhances Early Gastrointestinal Maturation in Young Turkey Poults - Moyle, J.R.; Santos, F. Solis de los; Huff, G.R.; Huff, W.E.; Rath, N.C.; Farnell, M.; Fanatico, A.C.; Ricke, S.C.; Enders, C.; Sonnenborn, U.; Donoghue, D.J.; Donoghue , A.M. (International Journal of Poultry Science, 2012)
Concerns over the use of antibiotics as growth promoters in poultry production has led to interest in finding alternative growth promoters such as natural compounds and probiotics. Supplementing feed with probiotics has shown to enhance the Gastrointestinal Tract (GIT) development of chickens and turkeys. The human probiotic, E. coli Nissle 1917 (EC Nissle) has been shown to stimulate innate immunity in mammals and to increase body weight in poultry. However, the effect of this probiotic on GIT development has not been studied. The objective of this study was to evaluate the effect of EC Nissle in the maturation of the GIT of young turkey poults. Fifty-four day of hatch turkey poults were housed in battery brooders and fed either a standard diet or the same diet containing of 108cfu EC Nissle /bird/day for 21 days. For GIT morphometric analysis, birds were euthanized on days 4, 7 or 21 and samples collected to evaluate villus height, villus surface area, lamina propria thickness, crypt depth and the number of neutral goblet cells. GIT morphometric analysis was conducted on duodenum, jejunum, ileum and cecum on days 4 and 7 and the duodenum on day 21. Villus height and villus surface of the GIT were higher in the EC Nissle treatments compared to control (p<0.05) on all sampling days with the exception of the jejunum and ileum on day 4. Lamina propria thickness and crypt depth were also increased in the EC Nissle treatment in all sections of the GIT except on day 4 in the jejunum. These data suggest that this human E. coli isolate enhanced the maturation of the GIT in young turkey poults and may have potential as an alternative to growth promoting antibiotics.